Assessment And Modelling Of Explosion Performance For Military Plastic Explosive (PE4) aND eMULEX eXPLOSIVE uNDER tEMPERATURE eFFECTS Using Artificial Neural Network (ANN) - Mohd Sharil Salleh (Tesis, 2025)
xx